Analisis Sistem Penganggaran dalam Manajemen keuangan Sekolah di SMAN 5 Payakumbuh - Fatma Sari; Hamdi Abdul Karim; Susanda Febriani (Manajemen Kreatif Jurnal, 2024)
The educational institutions at the moment are controlled in the financial management of schools in the educational institution. Therefore, in an educational institution it is very important to implement a system of guarantees in the financial management of the school so that the educational institutions can manage their finances effectively and effectively. The aim of this research is to look at the system of funding in the school’s financial management in SMAN 5. This research uses qualitative methodology, in particular using descriptive analysis and type of research case studies in the field. This research focuses on the theme of school education. Research findings suggest that budgetary planning has been proven effective by the existence of accurate manual accounting evidence and financial management carried out with the principles of openness and public accountability. Financial management at SMAN 5 Payakrasuh has successfully adopted the concept of openness and accountability in its internal reporting. It has been found that 85% of the money has been spent according to the planned.